The Tekoite Narrative and Retributive Justice: A Case Study on the Poliphony of Legal Discussions in the Hebrew Bible - Benke, László (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The Tekoite narrative (2 Samuel 14) is remarkable for its rhetorical skill and ideological complexity; as such, it is well suited to illuminate the rich tapestry of legal and ethical discussions preserved in Israel’s self-reflexive library we call the Hebrew Bible. With the overall aim of elucidating the Hebrew Bible’s dialectical polyphony on issues of rule enforcement and accountability – the theme of our conference section –, this paper attempts to map the legal concepts that are either embedded in the Tekoite narrative as integral elements of the worldview of the eighth to sixth-century Judahite community in which the narrative was created, or are reflected in the text as points to be evaluated or communicated. The paper arrives at two conclusions: first, it introduces the idea that the narrative served to reinforce the theme of retributive punishment by presenting an out-of-key, false iteration of the counter-theme of mercy, as relevant in the Hebrew Bible as the theme itself, and best embodied by Abraham’s plea for the undeserving in Genesis 18. And second, the paper suggests that a common lesson of the discussions of this theme and counter-theme, as they recur throughout the Hebrew Bible and also in the Tekoite narrative, is that it takes a prophet to judge properly when retributive justice can be set aside.